The clinical promise of immunotherapy in triple-negative breast cancer - Vikas P; Borcherding N; Zhang W (Cancer Management and Research, 2018)
Praveen Vikas,1,2 Nicholas Borcherding,2–5 Weizhou Zhang2–5 1Department of Internal Medicine, College of Medicine, University of Iowa, Iowa City, IA, USA; 2Holden Comprehensive Cancer Center, University of Iowa, Iowa City, IA, USA; 3Department of Pathology, College of Medicine, University of Iowa, Iowa City, IA, USA; 4Cancer Biology Graduate Program, College of Medicine, University of Iowa, Iowa City, IA, USA; 5Medical Scientist Training Program, College of Medicine, University of Iowa, Iowa City, IA, USA Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous disease with poorer outcomes compared to other breast cancer subtypes. Contributing to the worse prognosis in TNBC is the higher rates of relapse and rapid progression after relapse. Advances in targeted therapeutics and conventional chemotherapy for TNBC have been stymied due to the lack of specific targets. Moreover, the responses to chemotherapy in TNBC lack durability, partially accounting for the higher rates of relapse. Immunotherapy, notably immune-checkpoint blockade, has shown to improve survival and maintain robust antitumor responses in both hematologic and solid malignancies. Unlike lung cancer, melanoma, and bladder cancer, most breast cancers are not inherently immunogenic and typically have low T cell infiltration. However, among breast cancer subtypes, TNBC is characterized by greater tumor immune infiltrate and higher degree of stromal and intratumoral tumor-infiltrating lymphocytes (TILs), a predictive marker for responses to immunotherapy. Moreover, in TNBC, the high number of stromal TILs is predictive of more favorable survival outcomes and response to chemotherapy. Immunotherapy is being extensively explored in TNBC and clinical trials are showing some promising results. This article focuses on the rationale for immunotherapy in TNBC, to explore and discuss preclinical data, results from early clinical trials, and to summarize some ongoing trials. We will also discuss the potential application of immunotherapy in TNBC from a clinician’s perspective. Keywords: triple-negative breast cancer, immunotherapy, PD-1/PDL-1 antibody, CTLA-4 antibody, checkpoint inhibitors, cancer vaccines